Antioxidant Capacity, Phytochemical Profile, and Clustering of Pomegranate (Punica granatum L.) Peel Extracts Using Different Solvent Extraction - Rafi, Mohamad; Wulansari, Laela; Septaningsih, Dewi Anggraini; Purnomo, Tsania Firqin; Auliatifani, Reza; Khaydanur, Khaydanur; Ilmiawati, Auliya; Yulianti, Wina; Nengsih, Nunuk Kurniati; Suparto, Irma Herawati; Kusuma, Wisnu Ananta (Journal of Tropical Life Science, 2021)
Pomegranate has valuable nutritional content and contains various bioactive compounds, one found in the fruit's peel. The utilization of these bioactive compounds could be used as herbal medicines and supplements, such as antioxidants. This study aimed to determine the antioxidant capacity, phytochemical profile, and pomegranate peel extract grouping using different extracting solvents. The three extracting solvents used were water, 70% ethanol, and ethanol p.a. Antioxidant capacity of the three extracts was measured using the DPPH and CUPRAC methods. We also determined the total phenolic and flavonoid levels and the TLC fingerprint analysis and FTIR spectrum of the pomegranate peel extracts. The 70% ethanol extract owned the largest antioxidant capacity than the other two extracts with a value of 358.67 and 2981.59 Âµmol trolox/g dried sample using the DPPH and CUPRAC methods, respectively. The three pomegranate peel extracts' total phenolic and flavonoid levels ranged from 287.26â€“1068.81 mg GAE/g dried sample and 0.24-0.75 mg QE/g dried sample. TLC fingerprint analysis of pomegranate peel extract yielded 2, 6, and 6 bands for water extract, 70% ethanol, and p.a ethanol, respectively. The three extracts can be grouped based on FTIR spectrum data using principal component analysis using three principal components with a total variance of 93%. The results obtained show that using different extracting solvents provides different antioxidant capacities and phytochemical profiles.